Influência da laserterapia de baixa intensidade no processo regenerativo do músculo tibial anterior em ratos - Freitas, Carlos Eduardo Assumpção de [UNESP] (2015)
Recent research in the field of physiotherapy has aimed to elucidate the main changes involved in skeletal muscle regeneration after application of therapeutic resources. In this context, the application of Low Level Laser Therapy has proven to be effective at improving the muscle regeneration process. However, the type of laser, irradiation parameters, evaluation period and molecular mechanisms involved in the regeneration process present conflicting results. The aim of this study was to evaluate the effects of Low Level Laser Therapy, type GaAs at 904 nm, during the muscle regeneration process, for seven days after the lesion, and verify whether both the GaAs laser and chosen dose influence the muscle regeneration process. Thirty Wistar male adult rats (three-month old), mean body weight 210 - 340 g were used in this study. The animals were randomized into three groups: Control Group (C, n=10), Untreated Lesion Group (L, n=10) and Treated Lesion group (TL, n=10). After anesthetizing the animals, muscle lesion was induced by freezing (cryoinjury) in the middle belly portion of the tibialis anterior muscle (TA) of both hind limbs, using an iron rod previously immersed in liquid nitrogen. A GaAs laser, with a wavelength of 904 nm was used as a therapeutic resource. Daily laser applications were initiated 24 hours after lesion, with an energy density of 69 J/cm2, (48 seconds), for five consecutive days, at two points in the lesion area. On the seventh day, the animals were euthanized and weighed; the TA muscles from both hindlimbs were removed and processed for morphological and molecular analysis. The left TA muscle was frozen in liquid nitrogen and histological sections obtained in a cryostat were submitted to Hematoxylin and Eosin (for morphological analysis) and Picrosirius (for collagen analysis) staining. The right TA muscle was used for the analysis of gene expression of MyoD, myogenin, TNF-α and TGF-β by using the Polymerase...